Tongue pearl: A novel technique for treatment of an infant with median facial cleft and microcephaly - Sherif Essam Zahra; Mamdouh Aboul Hassan (Saudi Dental Journal)
This case report illustrates the presurgical treatment of a patient having a median facial cleft and microcephaly, using a guidance appliance. The appliance was custom designed and modified with a pearl-like acrylic structure attached to its lingual surface for pushing the extremely protruded tongue back to its normal position to facilitate anesthesia and surgical lip closure. Total treatment time was 5 weeks. Regaining normal tongue position, in turn, facilitated both intubation and extubation, preventing the postoperative respiratory distress the authors had experienced with similar cases. Keywords: Median facial cleft, Presurgical orthodontic treatment, Microcephaly, Guidance appliance